Case report: Primary pericardial angiosarcoma, a rare cause of cardiac tamponade - Kong, Ling-Yun; Cui, Xiao-Zheng; Xiang, Wei; Wang, Xiu-Juan; Liu, Fang (Frontiers in Cardiovascular Medicine, 2024)
Primary pericardial angiosarcoma is a rare malignancy of the pericardium. Its with variable clinical features and imaging characteristics remain unclear. Herein, we report a case of histopathologically confirmed pericardial angiosarcoma in a 66-year-old man. The patient developed cardiac tamponade in a short time period. His The transthoracic echocardiography showed multiple irregular echodensities heterogeneous in echogenicity encasing the apex of both ventricles in the pericardial spacehypo-echogenicities interrupted with hyper-echogenicity which encased the apex of both ventricles, and which was mistaken as for pericardial effusion initially. The patient died of cardiogenic shockcardiac arrest despite surgical pericardiectomy. Pericardial angiosarcoma can manifest as mass obliterating the pericardial sac, rather than pericardial effusion as usually seen on echocardiography. Multimodality imaging studies aid in the diagnosis of primary pericardial angiosarcoma but final diagnosis relies on tissue histopathology.